2022
DOI: 10.1021/acs.accounts.2c00515
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cinchona Alkaloids in the Enantio- and Diastereoselective Synthesis of Axially Chiral Compounds

Abstract: Conspectus Asymmetric synthesis using organic catalysts has evolved since it was first realized and defined. Nowadays, it can be considered a valid alternative to transition metal catalysis for synthesizing chiral molecules. According to the literature, the number of asymmetric organocatalytic processes associated with atropisomer synthesis has rapidly increased over the past 10 years because organocatalysis addresses the challenges posed by the most widespread strategies used for preparing axially chiral mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Injectable hydrogels provide a reliable approach for precise and sustained delivery of therapeutic agents into the joint cavity. , The thermosensitive hydrogel PLGA–PEG-PLGA was injected into the joint cavity at RT and rapidly transformed into a gel upon exposure to body temperature. The FDA-approved thermosensitive hydrogels based on PLGA copolymers have been widely utilized to deliver therapeutic or bioactive drugs and have broad prospects. The accumulation of metabolites derived from PLGA may elicit inflammatory response and expedite OA progression . However, certain studies did not observe a substantial inflammatory response induced by PLGA; thus, we believed that the local proinflammatory effects were weak and acceptable, which was confirmed in vivo and in vitro Moreover, PEG has been widely used in clinical trials and confirmed its safety in vivo . In vivo clinical trials of PLGA–PEG-PLGA are expected to fully confirm its safety and highlight the feasibility of widespread clinical application.…”
Section: Discussionmentioning
confidence: 64%
“…Injectable hydrogels provide a reliable approach for precise and sustained delivery of therapeutic agents into the joint cavity. , The thermosensitive hydrogel PLGA–PEG-PLGA was injected into the joint cavity at RT and rapidly transformed into a gel upon exposure to body temperature. The FDA-approved thermosensitive hydrogels based on PLGA copolymers have been widely utilized to deliver therapeutic or bioactive drugs and have broad prospects. The accumulation of metabolites derived from PLGA may elicit inflammatory response and expedite OA progression . However, certain studies did not observe a substantial inflammatory response induced by PLGA; thus, we believed that the local proinflammatory effects were weak and acceptable, which was confirmed in vivo and in vitro Moreover, PEG has been widely used in clinical trials and confirmed its safety in vivo . In vivo clinical trials of PLGA–PEG-PLGA are expected to fully confirm its safety and highlight the feasibility of widespread clinical application.…”
Section: Discussionmentioning
confidence: 64%
“…However, compared to the extensive studies on the synthesis of conventional atropisomers bearing a sole stereogenic axis (scenario I , Scheme 1b), the development of catalytic asymmetric reactions towards the synchronous control of axial and point chirality in one step has been much less studied and stands for a daunting task (scenario II ). 7,8 In this context, both issues of diastereo- and enantioselectivity need to be addressed properly to prevent the generation of a complex mixture of stereoisomers. Furthermore, it would be ideal and extremely desirable to establish catalyst-controlled diastereodivergent processes 9,10 that allow access to different diastereomers from identical starting materials (scenario III ), since individual diastereomers may exhibit significantly distinct biological activities against the same target.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we had previously overcome this problem by developing a protocol using silyldienol ethers, which allows us to achieve the desired result preferentially . Inspired by previous findings and our interest in the asymmetric synthesis of spiroindolines, we hypothesized that an organocatalyzed aza-Michael addition method that incorporates an intramolecular spiroannulation of an aminobenzyl moiety to a tethered cyclohexenone would lead to the generation of a quaternary stereocenter. To the best of our knowledge, such an organocatalytic enantioselective spirocyclization of cyclohexenone tethered anilines proceeding via an iminium ion has not been reported in the literature.…”
mentioning
confidence: 99%